Applications and trends of unmanned aerial vehicle in agriculture - CHEN Pengfei (浙江大学学报. 农业与生命科学版)
Unmanned aerial vehicle (UAV) has the characteristics of flexibility, not easily affected by weather condition, and can acquire high-resolution images when used to monitor crop growth status with mounted sensors. Thus, the UAV is of great significance to assist precision agriculture. In addition, the UAV can also be equipped with agricultural machinery to make field management, which can improve working efficiency and reduce disturbance to crop growth. In recent years, the application of UAV in agriculture has become a hot spot, and a series of studies have been conducted. However, in general, research in this area is still at its beginning phase. Therefore, we need to systematically summarize the application status of UAV and analyze existing problems, which can promote its better application in agriculture. This paper concluded the hardware equipment of agricultural UAV and its application status in some aspects, including plant growth monitoring, yield forecasting, nitrogen nutrition diagnosing, pests and diseases detecting and field management, and then put forward some development directions, in order to provide references for further research in related fields.